Interventions promoting recovery from depression for patients transitioning from outpatient mental health services to primary care: A scoping review. - Anne Sofie Aggestrup; Frederik Martiny; Line Lund Henriksen; Annette Sofie Davidsen; Klaus Martiny (PLoS ONE)
Introduction Major Depressive Disorder (MDD) is one of the most prevalent mental disorders worldwide with significant personal and public health consequences. After an episode of MDD, the likelihood of relapse is high. Therefore, there is a need for interventions that prevent relapse of depression when outpatient mental health care treatment has ended. This scoping review aimed to systematically map the evidence and identify knowledge gaps in interventions that aimed to promote recovery from MDD for patients transitioning from outpatient mental health services to primary care. Materials and methods We followed the guidance by Joanna Briggs Institute in tandem with the PRISMA extension for Scoping Reviews checklist. Four electronic databases were systematically searched using controlled index-or thesaurus terms and free text terms, as well as backward and forward citation tracking of included studies. The search strategy was based on the identification of any type of intervention, whether simple, multicomponent, or complex. Three authors independently screened for eligibility and extracted data. Results 18 studies were included for review. The studies had high heterogeneity in design, methods, sample size, recovery rating scales, and type of interventions. All studies used several elements in their interventions; however, the majority used cognitive behavioural therapy conducted in outpatient mental health services. No studies addressed the transitioning phase from outpatient mental health services to primary care. Most studies included patients during their outpatient mental health care treatment of MDD. Conclusions We identified several knowledge gaps. Recovery interventions for patients with MDD transitioning from outpatient mental health services to primary care are understudied. No studies addressed interventions in this transitioning phase or the patient's experience of the transitioning process. Research is needed to bridge this gap, both regarding interventions for patients transitioning from secondary to primary care, and patients' and health care professionals' experiences of the interventions and of what promotes recovery. Registration A protocol was prepared in advance and registered in Open Science Framework (https://osf.io/ah3sv), published in the medRxiv server (https://doi.org/10.1101/2022.10.06.22280499) and in PLOS ONE (https://doi.org/10.1371/journal.pone.0291559).